Epithelial–mesenchymal status influences how cells deposit fibrillin microfibrils - Baldwin, Andrew K. (The Company of Biologists, 2014)
Here, we show that epithelial–mesenchymal status influences how cells deposit extracellular matrix. Retinal pigmented epithelial (RPE) cells that expressed high levels of E-cadherin and had cell–cell junctions rich in zona occludens (ZO)-1, β-catenin and heparan sulfate, required syndecan-4 but not fibronectin or protein kinase C α (PKCα) to assemble extracellular matrix (fibrillin microfibrils and perlecan). In contrast, RPE cells that strongly expressed mesenchymal smooth muscle α-actin but little ZO-1 or E-cadherin, required fibronectin (like fibroblasts) and PKCα, but not syndecan-4. Integrins α5β1 and/or α8β1 and actomyosin tension were common requirements for microfibril deposition, as was heparan sulfate biosynthesis. TGFβ, which stimulates epithelial–mesenchymal transition, altered gene expression and overcame the dependency on syndecan-4 for microfibril deposition in epithelial RPE cells, whereas blocking cadherin interactions disrupted microfibril deposition. Renal podocytes had a transitional phenotype with pericellular β-catenin but little ZO-1; they required syndecan-4 and fibronectin for efficient microfibril deposition. Thus, epithelial–mesenchymal status modulates microfibril deposition.